Model Pembelajaran Pendidikan Agama Islam bagi Anak Berkebutuhan Khusus Tuna Wicara - Afifiani, Yessi Yustia; Husna, Difa’ul; Saputra, Rizki Nur Habib; Puspitasari, Desta Restu; Khasanah, Fatonatul (ANWARUL, 2023)
Every Indonesian citizen is given the opportunity to get an education, including those living in remote areas or children with special needs. Children with special needs actually have the same rights as other normal children. This special child actually also has the ability to continue to be developed. So that a child with special needs needs guidance and direction by an educator. This study aims to find out what are the learning models of Islamic Religious Education for children with special needs with speech impairments. The method used is Library Research (Library) with a qualitative approach. This technique is used to collect in-depth information and data by using various literature, documents or magazines related to the problems that occur. A child with special needs who is speech impaired is someone who has a disorder or obstacle in communicating. The learning curriculum used for children with special needs is different from other normal children, because there needs to be a special method that must be used to teach children with special needs so that the child can understand the material being presented.